1999
DOI: 10.1029/1999jc900004
|View full text |Cite
|
Sign up to set email alerts
|

Processes controlling the advance and retreat of sea ice in the Sea of Okhotsk

Abstract: Abstract. Using Defense Meteorological Satellite Program (DMSP) special sensor microwave imager (SSM/I) sea-ice data and meteorological data, we investigate processes controlling the advance and retreat of sea ice in the Sea of Okhotsk. For this investigation we apply a new algorithm to the SSM/I data, which is capable of calculating ice concentration and distinguishing sea-ice types; this algorithm is confirmed by comparison with National Oceanic and Atmospheric Administration (NOAA) advanced very high resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 18 publications
7
79
0
Order By: Relevance
“…Yamazaki (2000) and Ogi and Tachibana (2006) suggested significant influence of the North Atlantic Oscillation or Arctic Oscillation on the Okhotsk Sea ice. Kimura and Wakatsuchi (1999) revealed that the ice-edge advance coincides well with that predicted by 2% of the geostrophic wind, and concluded that the ice advance is determined primarily by wind through ice advection. The ice advance eventually ceases even if the prevailing northwesterly wind continues.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Yamazaki (2000) and Ogi and Tachibana (2006) suggested significant influence of the North Atlantic Oscillation or Arctic Oscillation on the Okhotsk Sea ice. Kimura and Wakatsuchi (1999) revealed that the ice-edge advance coincides well with that predicted by 2% of the geostrophic wind, and concluded that the ice advance is determined primarily by wind through ice advection. The ice advance eventually ceases even if the prevailing northwesterly wind continues.…”
Section: Introductionmentioning
confidence: 65%
“…This is reasonable since the sea ice advance is driven mainly by the prevailing northerly or northwesterly wind. Kimura and Wakatsuchi (1999) showed that the ice advance is explained by 2% of geostrophic wind for most years. However, in some years, such as in 1979 and 1980, the ice advance cannot be simply explained by the wind; in addition, the final ice advance or maximum ice extent cannot be explained by the wind (Kimura and Wakatsuchi 1999).…”
Section: Relationship Between Sea Ice Area and Heat Flux In The Late mentioning
confidence: 99%
See 1 more Smart Citation
“…showing the relationship between ice motion and the geostrophic wind over the Northern Hemisphere [Kimura and Wakatsuchi, 2000].…”
Section: Ssm/i Derived Daily Ice Motion We Have Presented Resultsmentioning
confidence: 99%
“…The largest range of modern sea ice expansion has reached the southeastern part of the Okhotsk Sea, near the Kuril Basin (Minervin et al, 2015). The expansion and retreat of modern sea ice are considerably affected by wind and temperature (Kimura and Wakatsuchi, 1999). Under the effect of wind and currents, sea ice drifts from the north to the southeast.…”
Section: Oceanographic Settingsmentioning
confidence: 99%